A calcium optimum for cytotoxic T lymphocyte and natural killer cell cytotoxicity. (12th March 2018) - Zhou, Xiao; Friedmann, Kim S.; Lyrmann, Hélène; Zhou, Yan; Schoppmeyer, Rouven; Knörck, Arne; Mang, Sebastian; Hoxha, Cora; Angenendt, Adrian; Backes, Christian S.; Mangerich, Carmen; Zhao, Renping; et al.
Abstract : Key points: Cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells are required to eliminate cancer cells. We analysed the Ca 2+ dependence of CTL and NK cell cytotoxicity and found that in particular CTLs have a very low optimum of [Ca 2+ ]i (between 122 and 334 nm ) and [Ca 2+ ]o (between 23 and 625 μm ) for efficient cancer cell elimination, well below blood plasma Ca 2+ levels. As predicted from these results, partial down‐regulation of the Ca 2+ channel Orai1 in CTLs paradoxically increases perforin‐dependent cancer cell killing. Lytic granule release at the immune synapse between CTLs and cancer cells has a Ca 2+ optimum compatible with this low Ca 2+ optimum for efficient cancer cell killing, whereas the Ca 2+ optimum for CTL migration is slightly higher and proliferation increases monotonously with increasing [Ca 2+ ]o . We propose that a partial inhibition of Ca 2+ signals by specific Orai1 blockers at submaximal concentrations could contribute to tumour elimination. Abstract: Cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells are required to protect the human body against cancer. Ca 2+ is a key metabolic factor for lymphocyte function and cancer homeostasis. We analysed the Ca 2+ dependence of CTL and NK cell cytotoxicity against cancer cells and found that CTLs have a bell‐shaped Ca 2+ dependence with an optimum for cancer cell elimination at rather low [Ca 2+ ]o (23–625 μm ) and [Ca 2+ ]i (122–334 nm ). This finding predicts that a partial inhibition of Orai1 should increase (rather than decrease) cytotoxicity of CTLs at [Ca 2+ ]o higher than 625 μm . We tested this hypothesis in CTLs and indeed found that partial down‐regulation of Orai1 by siRNA increases the efficiency of cancer cell killing. We found two mechanisms that may account for the Ca 2+ optimum of cancer cell killing: (1) migration velocity and persistence have a moderate optimum between 500 and 1000 μm [Ca 2+ ]o in CTLs, and (2) lytic granule release at the immune synapse between CTLs and cancer cells is increased at 146 μm compared to 3 or 800 μm, compatible with the Ca 2+ optimum for cancer cell killing. It has been demonstrated in many cancer cell types that Orai1‐dependent Ca 2+ signals enhance proliferation. We propose that a decrease of [Ca 2+ ]o or partial inhibition of Orai1 activity by selective blockers in the tumour microenvironment could efficiently reduce cancer growth by simultaneously increasing CTL and NK cell cytotoxicity and decreasing cancer cell proliferation. Abstract :  CTLs or NK cells kill cancer cells under three different conditions. At low Ca 2+ entry through Orai Ca 2+ channels and corresponding low intracellular [Ca 2+ ], cytotoxicity is not optimal and cancer cells are not efficiently eliminated (left). The same is true for high Ca 2+ entry and high intracellular [Ca 2+ ] (right). However, at intermediate Ca 2+ entry through Orai Ca 2+ channels and corresponding intermediate intracellular [Ca 2+ ], cytotoxic efficiency against cancer cells is optimal. Our data provide evidence that there is a calcium optimum for efficient CTL and NK cell cytotoxicity.